Arteriovenous Fistula in a Patient with Aberrant Radial Artery - S. Soni, Sachin; R. Barnela, Shriganesh; S. Saboo, Sonali; V. Deshpande, Ashish; S. Deshmukh, Shirish; V. Takalkar, Unmesh (Journal of Nephrology Advances, 2016)
Arteriovenous fistula is the most commonly used vascular access in patients on maintenance hemodialysis. Operating surgeon has to be aware about the normal anatomy of vessels as well as variations in the course of the vessels. Here wereport a case of radiocephalic arteriovenous fistula constructed in aberrant radial artery. This is the first case of arteriovenous fistula with aberrant radial artery to be reported in world literature.
Keywords: Arteriovenous Fistula; Aberrant Radial Artery; Hemodialysis; Vascular Access